Adverse effects of hyperbaric oxygen therapy: a systematic review and meta-analysis - Zhang, Yuyao; Zhou, Yijun; Jia, Yuanyuan; Wang, Tiantian; Meng, Dianhuai (Frontiers in Medicine, 2023)
ABSTRACT Introduction：Hyperbaric oxygen therapy is one of the common clinical treatments, but adverse effects have hampered and limited the clinical application and promotion of hyperbaric oxygen therapy. A systematic review and meta-analysis of the adverse effects of hyperbaric oxygen therapy have conducted by our group to provide a theoretical basis for clinical treatment. Methods：Three electronic databases (Pubmed, Web of Science, Cochrane) were comprehensively searched for randomized clinical trials (RCTs) from March, 2012 to October, 2022. Two reviewers independently screened titles and abstracts for eligibility and assessed the quality of the included studies. The meta-analysis was performed using RevMan 5.3. Results: A total of 24 RCTs involving 1497 participants were identified. ①HBOT group reported more adverse effects (30.11% vs 10.43%, P<0.05). ②The most frequent side effect of HBOT is ear discomfort (113 cases). ③When the courses of hyperbaric oxygen was >10 sessions, the incidence of adverse effects was higher than that of the control group; when the course of HBOT was ≤10 sessions, the adverse effects caused by hyperbaric oxygen were comparatively lower.④ When chamber pressures are above 2.0 ATA, the incidence of adverse effects is higher than that of the control group. While the chamber pressure is lower than 2.0 ATA, HBOT is relatively safe compared to the previous one. Conclusion: HBOT is more likely to cause adverse reactions when the chamber pressure is above 2.0 ATA. More attention should be paid to the possible occurrence of related adverse effects if the treatment course is ＞10 sessions. Systematic review registration: https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42022316605